2007
DOI: 10.1179/136485907x156924
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of artesunate plus either sulfadoxine–pyrimethamine or amodiaquine, for the treatment of uncomplicated,Plasmodium falciparummalaria in eastern Sudan

Abstract: Artemisinin-based combination therapy (ACT) is increasingly being adopted as the first-line treatment for malaria in sub-Saharan Africa. In September-November 2005, in New Halfa, eastern Sudan, the efficacy of artesunate-sulfadoxine-pyrimethamine (AS-SP) for the treatment of uncomplicated, Plasmodium falciparum was compared with that of artesunate-amodiaquine (AS-AQ). The artesunate was given at 4 mg/kg. day on days 0-2, with either a single dose of SP (25 mg sulfadoxine/kg) given on day 0, or AQ, at 10 mg/kg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The results obtained show that the AS+AQ association proved to be very effective with a ACPR rate adjusted by 97.2% in ITT and 98.3% in PP. Various studies conducted with artesunate/amodiaquine free combination, showed comparable efficacies with a non-inferiority to AL [13] and other formulations of ACT (artesunate/sulphadoxine-pyrimethamine, dihydroartemisinine/piperaquine, artesunate/chlorproguanil-Dapsone) [14-18]. This new paediatric formulation administered once a day, besides reducing the number of doses (usually twice a day) confirms the efficacy of this association [19].…”
Section: Discussionmentioning
confidence: 62%
“…The results obtained show that the AS+AQ association proved to be very effective with a ACPR rate adjusted by 97.2% in ITT and 98.3% in PP. Various studies conducted with artesunate/amodiaquine free combination, showed comparable efficacies with a non-inferiority to AL [13] and other formulations of ACT (artesunate/sulphadoxine-pyrimethamine, dihydroartemisinine/piperaquine, artesunate/chlorproguanil-Dapsone) [14-18]. This new paediatric formulation administered once a day, besides reducing the number of doses (usually twice a day) confirms the efficacy of this association [19].…”
Section: Discussionmentioning
confidence: 62%
“…SAEs were reported in 20 patients, of whom five were given intravenous quinine after referral to tertiary health facilities and subsequently recovered, suggesting a missed diagnosis of complicated malaria for which AL was not the appropriate treatment [20]. Rash, as reported here in 21 cases, is a recognized and frequent AE associated with artemesinin-based combination therapy [9,21-23]. There were 14 cases of AL treatment reported in pregnant women during the period described.…”
Section: Discussionmentioning
confidence: 97%
“…In Sudan, the current recommendation for uncomplicated malaria are AS/SP and AL as first and second-line treatment, respectively [5] with 100% efficacy in Damazin, Kosti, Malakal and New Halfa [6-9,17] and 99.3% in Kassala [7]. …”
Section: Discussionmentioning
confidence: 99%
“…There have been few studies on the efficacy of AS/SP [6-9] and only one published report on the efficacy of AL in Sudan [8]. Although these studies have reported high efficacy to both combinations, ranging from 99.8% to 100%, they did not show whether the small proportion of treatment failures was due to a recrudescence of existing parasites or acquisition of a new infection, except for one recent study which reported the PCR-corrected efficacy of AS/SP [9]. It was, therefore, decided to closely monitor patients for 28 days after treatment with AS/SP or AL, and the results were genotyped to indicate recrudescence versus new infections.…”
Section: Introductionmentioning
confidence: 99%